DARI PERSIA HINGGA CINA: Diskursus tentang Teori Kedatangan Islam di Melayu Nusantara - Lukmanul Hakim (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
The arrival of Islam in Malay Archipelago to this day is still a debate, because no data and facts have been found to be scientifically justified, but also because of the unilateral nature of the various theories. There is a strong tendency, certain theories emphasize only the specific aspects, while ignoring the other aspects. Therefore, most of the theories that exist in certain aspects fail to explain the coming of Islam, and the process of Islamization. This paper aims to analyze the theory of the arrival of Islam in the Malay Archipelago world. The method used is historical method. Until now there are at least four theories that discuss the theory of the arrival of Islam in the Malay Archipelago world. The four theories are Gujarat theory, Mecca theory, Persian theory and fourth theory (Chinese). Each of these theories has the strengths and weaknesses and certainly these four theories have a common view of Islam as a religion developed in the archipelago through a peaceful way and Islam does not recognize mission as practiced by Christians and Catholics.